Análises de desfechos de pacientes com Insuficiência Respiratória Aguda admitidos em Pronto Socorro e em Unidade de Pronto Atendimento do SUS de Belo Horizonte - Emanuele Gomes da Silva Lopes (2021)
The demand for emergency services has been growing in recent decades. Respiratory diseases are among the main causes that lead to the demand for the urgency and emergency system in Brazil. The ER (Emergency Room) needs minimal propaedeutic and / or therapeutic technological resources for the care of highly complex patients. The ECU (Emergency Care Unit), with an intermediate complexity located between Basic Health Care and Hospital Care, has been the gateway for highly complex patients who need an adequate hospital structure for this care. It is common for patients to spend hours waiting for transfer to Intensive Care Units (ICUs), even with complex clinical conditions. Objective: The aim of this study was to evaluate the outcome of patients with ARF (Acute Respiratory Insufficiency) admitted to the Emergency Room and the Emergency Care Unit. The time until transfer to the ICU was also assessed. Associations between place of initial care and length of stay in the ICU, time on artificial ventilation and mortality were verified. Method: 488 patients admitted with IRPA in ER and in ECU, aged 18 years or older, were followed up sequentially. Data collection was performed through the analysis of medical records with insertion of information in a standard form with the variables necessary for the study. APACHE II and SAPS 3 were analyzed as severity scores for patients. Results: There was a long waiting time for transfer to the ICU among surviving patients (median = 31.67 hours). Mortality in the emergency room was higher in the ECU (25.6%) compared to the ER (15.3%). Patients admitted to the ECU were more severe than those admitted to the ER. After multivariate analysis, the place of initial care was not independently associated with death. The higher mortality in the ECU in relation to the ER was explained by the difference in severity of the patients. After multivariate analysis, it was observed that the initial care location was independently associated with ICU mortality. Conclusion: Different outcomes were observed according to the place of initial care in patients with ARF, which allows identifying opportunities for optimization in health care for individuals admitted to emergency services. It is proposed to create strategies and protocols in institutions and in medical regulation that will surely have an impact on the safety and quality of care provided.